Candidate Molecular Compounds as Potential Indicators for Meibomian Gland Dysfunction - Asiedu, Kofi (Frontiers in Medicine, 2022)
Meibomian gland dysfunction is the leading cause of dry eye disease throughout the world. Studies have shown that several molecules, including but not limited to interleukins, amino acids, cadherins, eicosanoids, carbohydrates, proteins, and many others, are altered in meibomian gland dysfunction compared to healthy normal controls. Some of these molecules also show differences in concentrations in tears between meibomian gland dysfunction and dry eye disease, further boosting hopes as candidate biomarkers. MGD is a complex condition, making it difficult to distinguish patients using single biomarkers. Therefore, multiple biomarkers forming a multiplex panel may be required.